Think Piece: Trust as a foundation for ethics and integrity in educational contexts - Eaton, Sarah Elaine (Critical Studies in Teaching and Learning, 2025)
Trust has been a central theme in academic integrity discourse for decades. In this piece, I think about trust from a variety of perspectives: student conduct, faculty conduct, and organizational trust. I then discuss the role of trust in addressing misconduct. These framings are drawn from a model of Comprehensive Academic Integrity (CAI), in which academic integrity includes and extends beyond student conduct.